2020
DOI: 10.1016/j.jvoice.2018.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Lung Volume on the Electroglottographic Waveform in Trained Female Singers

Abstract: Objectives. To determine if in singing there is an effect of lung volume on the electroglottographic waveform, and if so, how it varies over the voice range. Study design. Eight trained female singers sang the tune "Fr ere Jacques" in 18 conditions: three phonetic contexts, three dynamic levels, and high or low lung volume. Conditions were randomized and replicated. Methods. The audio and EGG signals were recorded in synchrony with signals tracking respiration and vertical larynx position. The first 10 Fourier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Singing is considered a type of human expression [9] [10] [11] and a complicated procedure that can be influenced by physical, psychological, environmental social and cultural factors [9] [12] [13] [14] [15]. Several researchers have attempted to quantify the factors that influence and constitute this phenomenon, as well as the morphometric and physiological characteristics of the larynx, while singing takes place [16]- [22].…”
Section: Introductionmentioning
confidence: 99%
“…Singing is considered a type of human expression [9] [10] [11] and a complicated procedure that can be influenced by physical, psychological, environmental social and cultural factors [9] [12] [13] [14] [15]. Several researchers have attempted to quantify the factors that influence and constitute this phenomenon, as well as the morphometric and physiological characteristics of the larynx, while singing takes place [16]- [22].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, other studies have suggested that there is a relationship between laryngeal size (length, shape and thickness of the vocal folds) and qualitative vocal characteristics (pitch, loudness and timbre), as they are observed clinically by vocal coaches and ENT doctors. The morphological characteristics of the vocal folds seem to differ between voice categories, and affect the voice production while singing [18] [19] [20] [21]. Our purpose was to evaluate the vocal folds' characteristics, using the examination method of stroboscopy.…”
Section: Introductionmentioning
confidence: 99%
“…In any nonempty cell, one to several hundred phonatory cycles may be represented. It has been shown that voices on repeated visits to the same f o and SPL tend to be quite consistent (Ternström et al, 2020). Provided that the voice production settings remain generally constant during the recording, a parameter mean in a cell only becomes more stable (i.e., smaller confidence interval and standard error) as more phonatory cycles are accumulated.…”
mentioning
confidence: 99%
“…Voice maps are thus easy to interpret qualitatively on visual inspection, and they render a wealth of numeric data in a compact form across the voice range. Furthermore, mapped data can be compared quantitatively across groups and/or conditions (Lã & Ternström, 2020;Ternström et al, 2020). Voice-mapping technology also affords real-time visual feedback, which is helpful for eliciting the desired productions from the participants (Hallin et al, 2012;Holmberg et al, 2007) across the targeted voice range.…”
mentioning
confidence: 99%
See 1 more Smart Citation